2019
DOI: 10.1186/s12933-019-0932-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of body weight and diabetes on new-onset atrial fibrillation: a nationwide population based study

Abstract: Background Being obese or underweight, and having diabetes are important risk factors for new-onset atrial fibrillation (AF). However, it is unclear whether there is any interaction between body weight and diabetes in regard to development of new-onset AF. We aimed to evaluate the role of body weight status and various stage of diabetes on new-onset AF. Methods This was a nationwide population based study using National Health Insura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 36 publications
(36 reference statements)
1
45
0
1
Order By: Relevance
“…It has been hypothesized that metabolic syndrome causes a transformation of the epicardial adipose tissue leading to proinflammatory mediators causing endothelial dysfunction, and fibrosis, which in turn leads to the development of structural and electrical atrial remodelling [30][31][32][33]. In a nationwide populationbased study, body weight status and diabetes had synergistic effects on the risk of new-onset atrial fibrillation [34]. Animal studies confirms that insulin resistance was associated with various aspects of remodelling in the atria, proposing that these might share common electrical and structural remodelling processes in the atria [35].…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that metabolic syndrome causes a transformation of the epicardial adipose tissue leading to proinflammatory mediators causing endothelial dysfunction, and fibrosis, which in turn leads to the development of structural and electrical atrial remodelling [30][31][32][33]. In a nationwide populationbased study, body weight status and diabetes had synergistic effects on the risk of new-onset atrial fibrillation [34]. Animal studies confirms that insulin resistance was associated with various aspects of remodelling in the atria, proposing that these might share common electrical and structural remodelling processes in the atria [35].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also reported adrenergic activation and heterogeneous sympathetic innervation in diabetic hearts, suggesting that neural remodeling may play a crucial role in diabetes-related atrial arrhythmia [ 28 ]. Furthermore, T2DM itself is associated with several chronic diseases including obesity, hypertension, chronic kidney disease, and heart failure, all of which further increase the risk of incident AF [ 6 , 7 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has become a major health problem worldwide and affects almost all of the major cardiovascular risk factors including hypertension, type-2 diabetes mellitus (T2DM), and hyperlipidemia [1][2][3][4][5]. Although obesity is associated with an increased risk of cardiovascular diseases (CVDs) and CVD-related risk factors [3], relevant epidemiologic studies have demonstrated obese or overweight T2DM patients may have better clinical outcomes compared with those at a normal weight [6,7]. Relevant studies have indicated that this phenomenon is partly attributed to the fact that body mass index (BMI) is an imperfect measure of obesity; additionally, BMI does not reflect body fat distribution and does not discriminate lean body mass from visceral adipose tissue [8,9].…”
Section: Introductionmentioning
confidence: 99%